The quality of life among diabetes mellitus type 2 geriatric patients at diabetic centre Hospital Universiti Sains Malaysia (USM) Kubang Kerian, Kelantan - Hashim, Norhamizah (Universiti Sains Malaysia, 2013)
Diabetes Mellitus is one of the disease that affect elderly mostly over 60 years old. Complications related to diabetes affect elderly such as neuropathy, retinopathy, and many complications related. These may affect their quality of life such as in physical functioning. The metabolic control also provides a guideline whether DM’s patients adhere to the treatment, medication and diet in order to improve their Quality of Life. The aim of this study is to determine the level of Quality of life among elderly diabetes mellitus type 2. Apart from that, it is conducted to determine the association of demographical data and metabolic control (HbAlc) with quality of life among elderly at Diabetic Centre Hospital USM. Respondent were taken via purposive sampling method among geriatric patients, aged 60 and above who attended Diabetic Centre Hospital USM (n=70). Data from interview based on questionnaire which consists of socio-demographical data, metabolic control (HbAlc value) and WHOQOL-BREF were collected in 5 weeks and processed by using Statistical Package for Social Science (SPSS) version 20, with the p-value of 0.05 for Chi-Square Test. From the study, 22.9% respondents stated that their quality of life is good while 77.1% are moderate. From the result obtained, there is no significant different between selected demographical data which is sex (p=0.511), age (p—0.436), race (p—0.229), educational level (p= > 0.950), financial sources (p=0.105), metabolic control (p=0.105), with quality of life. As a conclusion, the future research should be conducted by including larger sample size and at other institution to see whether it related to quality of life among elderly or not. Furthermore, most of the findings revealed that health education must be delivered effectively by health care provider for an elderly with diabetes in order to improve their metabolic control, preventing from complication of diabetes and improving their quality of life.